Correlates of Antiretroviral Therapy Adherence among HIV-Infected Older Adults. (May 2016) - McCoy, Katryna; Waldrop-Valverde, Drenna; Balderson, Benjamin H.; Mahoney, Christine; Catz, Sheryl
Background: Despite the success of antiretroviral therapy (ART), HIV-infected older African Americans experience higher mortality rates compared to their white counterparts. This disparity may be partly attributable to the differences in ART adherence by different racial and gender groups. The purpose of this study was to describe demographic, psychosocial, and HIV disease-related factors that influence ART adherence and to determine whether race and gender impact ART adherence among HIV-infected adults aged 50 years and older. Methods: This descriptive study involved a secondary analysis of baseline data from 426 participants in "PRIME, " a telephone-based ART adherence and quality-of-life intervention trial. Logistic regression was used to examine the association between independent variables and ART adherence. Results: Higher annual income and increased self-efficacy were associated with being ≥95% ART adherent. Race and gender were not associated with ART adherence. Conclusion: These findings indicated that improvements in self-efficacy for taking ART may be an effective strategy to improve adherence regardless of race or gender.